Quantum enhanced kHz gravitational wave detector with internal squeezing. (5th March 2020) - Adya, V B; Yap, M J; Töyrä, D; McRae, T G; Altin, P A; Sarre, L K; Meijerink, M; Kijbunchoo, N; Slagmolen, B J J; Ward, R L; McClelland, D E
Abstract: We propose adding a nonlinear element to a long signal recycling cavity to enhance the high-frequency sensitivity (900 Hz–5 kHz) of a kilometer-scale interferometric gravitational wave detector. Using numbers for absorption and scattering losses in the detector consistent with advanced LIGO+, we demonstrate a factor of 3.5 improvement in quantum noise limited strain sensitivity in the kHz regime. Such a configuration is robust to internal losses and reduces the requirement on the amount of circulating power in the detector to achieve sensitivity comparable to future gravitational wave detectors. This proposed configuration is compatible with the existing gravitational wave detector vacuum infrastructure and could enable exploration of exotic science, such as observing the merger phase of binary neutron stars, which in turn may provide constraints on the neutron star equation of state.